"Decision-critical" work: a conceptual framework. Issue 1 (December 2016) - Fan, Xiangning; Els, Charl; Corbet, Kenneth; Straube, Sebastian
Abstract "Safety-sensitive" workers, also termed "safety-critical" workers, have been subject to fitness to work assessments due to concerns that a performance error may result in worker injury, injury to coworkers or the general public, and/or disruption of equipment, production or the environment. However, there exists an additional category of "decision-critical" workers, distinct from "safety-sensitive" workers, in whom impairment may impact workplace performance, relationships, attendance, reliability and quality. Adverse consequences in these latter areas may not be immediately apparent, but a potential "orbit of harm" nevertheless exists. Workplace consequences arising from impairment in "decision-critical" workers differ from those in "safety-sensitive" personnel. Despite their importance in the occupational context, "decision-critical" workers have not previously been differentiated from other workers in the published literature, and we now outline an approach to fitness to work assessment in this group.